2019
DOI: 10.1007/s40265-018-1019-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hepatic Encephalopathy in Cirrhosis on Quality-of-Life Issues

Abstract: Hepatic encephalopathy (HE) has a major impact on health-related quality of life (HRQOL) in patients, which has clinical and psychosocial consequences. HRQOL in cirrhosis has been measured by generic and liver-specific instruments, with most studies indicating a negative impact of HE. HRQOL abnormalities span daily functioning, sleep–wake cycle changes, and the ability to work. Of these, sleep–wake cycle changes have a major effect on HRQOL, which remains challenging to treat. The personal effect of HRQOL is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 53 publications
2
40
0
3
Order By: Relevance
“…Especially the limited activity, the worries and the emotional function correlate with the psychosocial stress. It is known that especially cognitive defects and reduction of vigilance, as in hepatic encephalopathy, have an influence on the psychosocial burden on relatives [15]. In our study the presence of hepatic encephalopathy was confirmed as an influencing factor to increase the burden on relatives.…”
Section: Discussionsupporting
confidence: 72%
“…Especially the limited activity, the worries and the emotional function correlate with the psychosocial stress. It is known that especially cognitive defects and reduction of vigilance, as in hepatic encephalopathy, have an influence on the psychosocial burden on relatives [15]. In our study the presence of hepatic encephalopathy was confirmed as an influencing factor to increase the burden on relatives.…”
Section: Discussionsupporting
confidence: 72%
“…Caregivers of patients with HE can face substantial financial and psychological burdens that may affect personal health and longevity. The authors make a plea for the regular assessment of HRQOL in this population [2].…”
mentioning
confidence: 99%
“…( 12,33 ) Collectively, these findings indicate that it may be time to consider PROs in the evaluation of patients with cirrhosis. ( 34 )…”
Section: Discussionmentioning
confidence: 99%